Desain Geometri Lereng Optimal Pada Rencana Penggalian Ulang Material Timbunan Berdasarkan Parameter Geoteknik Melalui Pendekatan Tingkat Pemadatan Timbunan - Melodi, Aldo; Ibrahim, Eddy; Komar, Syamsul (Dinasti Research, 2025)
This study analyzes the slope stability in Pit X of PT Bukit Asam, Tbk (PTBA), which is a former disposal area that has been re-excavated, resulting in the presence of old dump material. The objective of this study is to analyze and process the material properties used in assessing the slope stability in Pit X and to determine the optimal overall slope geometry for Pit X. In this study, the determination of material properties for slope stability analysis in Pit X was carried out by creating cross-sections, considering the position of boreholes, and processing material properties from the nearest borehole data using a class creation and interval creation approach for each material property. The material properties used are the median values of each class. The most optimal overall slope geometry consists of a single bench height of 6 meters, a single bench width of 12 meters (1:2 ratio), and a bench width of 23 meters. This slope geometry was applied to all cross-sections, resulting in a dynamic factor of safety (FoS) of 1.216 and a static FoS of 1.393 for cross-section A-A', a dynamic FoS of 1.552 and a static FoS of 2.016 for cross-section B-B', a dynamic FoS of 1.529 and a static FoS of 1.760 for cross-section C-C', and a dynamic FoS of 1.585 and a static FoS of 1.827 for cross-section D-D', all of which are considered safe. These FoS values were obtained under conditions immediately after rainfall had ceased, with a recorded rainfall intensity of 110.08 mm and a duration of 4.18 hours.